Modification of the Method of Least Squares - Silvestrov, Anton; M'yakshylo, Olena; Kryvoboka, Halyna (My University, 2019)
The article deals with the problems of using a focused multilevel information system in optimal management. In order to make such a system more efficient, it is proposed to modify the least-squares method, which provides unbiased estimates of the parameters in the real situation of noisy measurements of input and output signals of the primary converters. Parameters are estimated using the proposed method, which ensures smoothing of external influences of the model under study on the results. The efficiency of the considered method is confirmed by comparison with the method of least squares
Keywords: рarametric identification; параметрична ідентифікація; ordinary least squares; звичайні найменші квадрати; unbiasedness; неупередженість; estimation efficiency; оцінка ефективності; modification of ordinary least squares; модифікація звичайних найменших квадратів; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки